Astragaloside IV ameliorates experimental autoimmune myasthenia gravis by regulating CD4 + T cells and altering gut microbiota - Senhui Weng; Linwen Huang; Bingxing Cai; Long He; Shuting Wen; Jinghao Li; Zhuotai Zhong; Haiyan Zhang; Chongyang Huang; Yunying Yang; Qilong Jiang; Fengbin Liu (BMC, 2023)
Abstract Background Myasthenia gravis (MG) is an antibody-mediated autoimmune disease and its pathogenesis is closely related to CD4 + T cells. In recent years, gut microbiota is considered to play an important role in the pathogenesis of MG. Astragaloside IV (AS-IV) is one of the main active components extracted from Astragalus membranaceus and has immunomodulatory effects. To study the immunomodulatory effect of AS-IV and the changes of gut microbiota on experimental autoimmune myasthenia gravis (EAMG) mice, we explore the possible mechanism of AS-IV in improving MG. Methods In this study, network pharmacology was utilized to screen the crucial targets of AS-IV in the treatment of MG. Subsequently, a Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis was performed to identify potential pathways through which AS-IV acts against MG. Furthermore, experimental investigations were conducted to validate the underlying mechanism of AS-IV in MG treatment. Before modeling, 5 mice were randomly selected as the control group (CFA group), and the other 10 were induced to EAMG model. These mice were randomly divided into EAMG group and EAMG + AS-IV group, n = 5/group. In EAMG + AS-IV group, AS-IV was administered by gavage. CFA and EAMG groups were given the same volume of PBS. Body weight, grip strength and clinical symptoms were assessed and recorded weekly. At the last administration, the feces were collected for 16S RNA microbiota analysis. The levels of Treg, Th1 and Th17 cells in spleen and Th1 and Th17 cells in thymus were detected by flow cytometry. The levels of IFN-γ, IL-17 and TGF-β in serum were measured by ELISA. Furthermore, fecal microbial transplantation (FMT) experiments were performed for exploring the influence of changed intestinal flora on EAMG. After EAMG model was induced, the mice were treated with antibiotics daily for 4 weeks to germ-free. Then germ-free EAMG mice were randomly divided into two groups: FMT EAMG group, FMT AS-IV group, n = 3/group. Fecal extractions from EAMG and EAMG + AS-IV groups as gathered above were used to administered daily to the respective groups for 4 weeks. Body weight, grip strength and clinical symptoms were assessed and recorded weekly. The levels of Treg, Th1 and Th17 cells in spleen and Th1 and Th17 cells in thymus were detected at the last administration. The levels of IFN-γ, IL-17 and TGF-β in serum were measured by ELISA. Results The network pharmacology and KEGG pathway analysis revealed that AS-IV regulates T cell pathways, including T cell receptor signaling pathway and Th17 cell differentiation, suggesting its potential in improving MG. Further experimental verification demonstrated that AS-IV administration improved muscle strength and body weight, reduced the level of Th1 and Th17 cells, enhanced the level of Treg cells, and resulted in alterations of the gut microbiota, including changes in beta diversity, the Firmicutes/Bacteroidetes (F/B) ratio, and the abundance of Clostridia in EAMG mice. We further conducted FMT tests and demonstrated that the EAMG Abx-treated mice which were transplanted the feces of mice treated with AS-IV significantly alleviated myasthenia symptoms, reduced Th1 and Th17 cells levels, and increased Treg cell levels. Conclusion This study speculated that AS-IV ameliorates EAMG by regulating CD4 + T cells and altering the structure and species of gut microbiota of EAMG.